Involvement of Lys 62[217] and Lys 63[218] of Human Anticoagulant Protein C in Heparin Stimulation of Inhibition by the Protein C Inhibitor - Shen, Lei; Villoutreix, Bruno O.; Dahlbäck, Björn (Thrombosis and Haemostasis, 1999)
Inhibition of activated protein C (APC) by protein C inhibitor (PCI) is stimulated by heparin, whereas inhibition by α1-antitrypsin (AAT) is heparin-independent. Three lysine residues located in a positively charged cluster in the serine protease domain of protein C (PC) were mutated to probe their involvement in the heparin stimulation of inhibition by PCI. These mutations were selected after analysis of the three-dimensional structure of APC and of molecular models for PCI and the APC-PCI complex. A double mutant, K62[217]N/K63[218]D, a single mutant, K86[241]S, and wild-type PC were expressed in embryonic human kidney 293 cells. Heparin stimulated the rate of inhibition of wt-APC by PCI approximately 400-fold, with second order rate constants (k2) in the absence and presence of heparin of 0.72 × 103 M–1s–1 and 2.87 × 105 M–1s–1, respectively. In contrast, heparin only yielded a 52-fold stimulation of the rate of inhibition of the double mutant APC by PCI as the rate constants in the absence and presence of heparin were k2 = 2.44 × 103 M–1s–1 and k2 = 1.26 × 105 M–1s–1, respectively. The double mutant K62N/K63D eluted at approximately 10% lower NaCl concentration from a heparin Sepharose column than the K86S mutant or wt-APC. These data suggest K62 and K63 in APC to be part of a heparin binding site which is important for heparin-mediated stimulation of inhibition of APC by PCI.Abbreviations: APC, activated protein C; PC, protein C; PCI, protein C inhibitor, AAT, α1-antitrypsin also called α1-proteinase inhibitor, AT, antithrombin; TM, thrombomodulin. The chymotrypsinogen nomenclature for APC (1) is used in the text while the PC numbering is indicated between brackets whenever appropriate. P1, P2... and P1’, P2’.. designate inhibitor residues amino- and carboxy-terminal to the scissile peptide bond, respectively, and S1, S2.. and S1’, S2’.. the corresponding subsites of the protease (2). The antitrypsin numbering (3) for PCI is used along this article while the PCI numbering is mentioned between brackets whenever appropriate.